2022
DOI: 10.1038/s41545-022-00150-9
|View full text |Cite
|
Sign up to set email alerts
|

TiO2 nanotube electrode for organic degradation coupled with flow-electrode capacitive deionization for brackish water desalination

Abstract: A photoelectrochemical (PEC) oxidation and flow-electrode capacitive deionization (FCDI) dual system was explored for the effective treatment of brackish water. Two anodic electrodes with electrochemically self-doped TiO2 arrays (blue-mesh/ blue-plate TiO2 nanotube arrays (BM-TNA & BP-TNA)) were fabricated by annealing at 600 °C, and applied for the treatment of a water system. Specifically, the BM-TNA confirmed lower electrical resistance and superior performance under multiple light source (UV-A, -B, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The other study achieved P recovery efficiencies of 62% over 96 h continuous operation using AC flow electrodes . A few studies examined flow electrodes involving redox reactions to enhance the oxidation of contaminants and desalination. Flow electrodes have also been integrated into microbial electrochemical systems to promote electron harvesting efficiencies more than stationary (bio)­electrodes. , However, no study has examined AC-based flow electrodes for catalytic reactions, such as HER in MECs.…”
Section: Introductionmentioning
confidence: 99%
“…The other study achieved P recovery efficiencies of 62% over 96 h continuous operation using AC flow electrodes . A few studies examined flow electrodes involving redox reactions to enhance the oxidation of contaminants and desalination. Flow electrodes have also been integrated into microbial electrochemical systems to promote electron harvesting efficiencies more than stationary (bio)­electrodes. , However, no study has examined AC-based flow electrodes for catalytic reactions, such as HER in MECs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a submerged-type FCDI system was realized by utilizing a multi flow-electrode cartridge chamber configuration (Figure 9a). 44 The system inverses the common conception of the feed chamber being placed between two flow-electrode chambers as adopted in conventional FCDI modules and instead introduced cartridge-type flow-electrode chambers with alternating anode and cathode chambers to be submerged within a feed tank, which maximizes the effective contact area between the feed solution and the flow-electrode. Another novel design resembling a hollow-fiber membrane module for a conventional membrane separation process was suggested, with the tubular flow-channels functioning as the flowelectrode chamber (Figure 9b).…”
Section: Modeling Comparison Of the Swro And Fcdi Processesmentioning
confidence: 99%
“…Its many unique properties, such as its large bandgap (3.0–3.5 eV) and nontoxicity, render it useful for numerous applications. More specifically, it has been demonstrated that UV irradiation of TiO 2 NTs produces reactive oxygen species such as hydroxyl and superoxide radicals, allowing for the degradation of compounds such as rhodamine B, bisphenol A, and sulfamethoxazole . TiO 2 NTs are normally fabricated through an anodization process ,, using both Ti and an otherwise inert electrode.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, it has been demonstrated that UV irradiation of TiO 2 NTs produces reactive oxygen species such as hydroxyl and superoxide radicals, 3 allowing for the degradation of compounds such as rhodamine B, 23 bisphenol A, and sulfamethoxazole. 24 TiO 2 NTs are normally fabricated through an anodization process 4,12,13 using both Ti and an otherwise inert electrode. The TiO 2 NT growth process which utilizes an ionic fluoride compound can be described by the following chemical reactions:…”
Section: ■ Introductionmentioning
confidence: 99%